ANALYSIS OF ELEMENTARY SCHOOL STUDENTS' THINKING ABILITIES BASED ON SOLO TAXONOMY IN SOLVING HOTS MATHEMATICS PROBLEMS - Jamaluddin; Hamriani; Sri Hudaya; Hamda; Syahrul syawal (STMIK Indonesia Banda Aceh, 2026)
The low level of higher-order thinking skills among elementary school students in mathematics remains a significant concern that demands systematic and in-depth examination. This study aims to: (1) describe the profile of elementary students' thinking abilities based on the Structure of Observed Learning Outcomes (SOLO) taxonomy; (2) identify the dominant SOLO taxonomy level achieved by students in solving mathematical Higher Order Thinking Skills (HOTS) problems; and (3) analyze the factors contributing to differences in students' SOLO taxonomy levels. This study employs a literature review method (library research) with a qualitative content analysis approach applied to ten relevant and verified scientific sources. The findings reveal that the thinking ability profile of elementary school students is predominantly concentrated at the multistructural level, where students can utilize more than one piece of information but are unable to integrate it comprehensively and coherently. Achievement at the relational and extended abstract levels remains considerably limited. Factors influencing these variations include cognitive style, metacognitive ability, prior mathematical knowledge, and instructional methods applied by teachers. This study affirms that the SOLO taxonomy serves as an effective diagnostic instrument for mapping the quality of students' thinking in a hierarchical and comprehensive manner.